Cigarette Smoke Exposure, but Not High Fat Diet, is Able to Induce Atherosclerosis in Wild-Type Rats - Qorry Amanda; Nyoman Suci Widyastiti; Yan Wisnu Prajoko; Nani Maharani; Udin Bahrudin (Journal of Biomedicine and Translational Research, 2022)
Background: High-fat diet (HFD) and cigarette smoke exposure (CSE) have been used to induce atherosclerosis in wild-type (WT) rats however, their effectivity remains unclear.Objective: To confirm and compare the effectivity of HFD and CSE on both the histopathology of aorta and the level of malondialdehyde (MDA) in WT rats.Methods: Thirty-six WT Wistar rats were divided into four main groups (K0, K1, K2, and K3) and four subgroups (K3A, K3B, K3C, and K3D). The negative control group (K0) was fed with regular diet. Group K1 was treated with an intravenous adrenaline followed by high-fat diet (HFD), K2 was fed with regular diet and given CSE, while K3 was treated with a combination of CSE and HFD. The serum and cardiac MDA levels were measured using ELISA. Hematoxylin eosin and oil red O staining of aorta were done for measuring of the intima-media thickness (IMT) ratio and for counting of foam cells, respectively. Results: Both serum and cardiac tissue MDA levels in either K1, K2, or K3 were significant higher (p<0.01) than that of in K0. IMT ratio in K3 was significant higher compared to other groups (p<0.01). Foam cell numbers were significant higher in K2 and K3 groups than that of in either K0 or K1 (p<0.01).Conclusion: While the HFD fails to induce atherosclerosis in WT rats for 28 days, either CSE or combination of CSE and HFD is able to induce it, and the combination is better than alone.